PENGENALAN PELUANG PASAR GLOBAL ERA DIGITAL DI DESA GANDATAPA - Pramono, Agus; Musarofah, Ani; Naila Rohmah, Andin; Saputra, Ade; Fadil Abdillah, Hanif (Jurnal Abdi Nusa, 2024)
Technological developments in the digital era greatly influence the sharing of life, one of which is the field of marketing the goods and services sector in the era of globalization. This article aims to educate and explore how citizens in remote villages can participate in taking advantage of existing developments by improving quality and knowledge in product development and marketing globally utilizing advances in communication and information in the digital era. This service identifies the introduction of global markets and the opportunities therein by maximizing the use of current digital technology. These findings provide in-depth insight into global markets and open new doors to opportunities for Gandatapa residents.